2012
DOI: 10.1016/j.trstmh.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of soil-transmitted helminthiasis in an Amazonic community of Peru using multiple diagnostic techniques

Abstract: An observational descriptive study was conducted in a Shipibo-Conibo/Ese'Eja community of the rainforest in Peru to compare the Kato-Katz method and the spontaneous sedimentation in tube technique (SSTT) for the diagnosis of intestinal parasites as well as to report the prevalence of soil-transmitted helminth (STH) infections in this area. A total of 73 stool samples were collected and analysed by several parasitological techniques, including Kato-Katz, SSTT, modified Baermann technique (MBT), agar plate cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 22 publications
5
54
4
2
Order By: Relevance
“…In the present study, around 24 (4.43%) of 542 individuals from six indigenous villages were positive for S. stercoralis larvae (Figure 1) which is roughly similar to results reported in other studies in indigenous communities in Brazil, for instance in Parakanã Indians (5.6%) from State of Pará, in Maxakali Indians, from State of Minas Gerais (5.4%), in members of the ethnic group Terena from State of Mato Grosso do Sul (3.8 %) and in Suruí Indians (0.5 %) [8,10,11,12]. Our results are also in agreement with studies performed in other regions worldwide [13,14]. The rate of infestation, in the present study, could be related to a number of factors such as poor hygiene, inadequate sanitation, water intake that was neither filtered nor chlorinated, low education, low socioeconomic status [15,16,17,18].…”
Section: Resultssupporting
confidence: 93%
“…In the present study, around 24 (4.43%) of 542 individuals from six indigenous villages were positive for S. stercoralis larvae (Figure 1) which is roughly similar to results reported in other studies in indigenous communities in Brazil, for instance in Parakanã Indians (5.6%) from State of Pará, in Maxakali Indians, from State of Minas Gerais (5.4%), in members of the ethnic group Terena from State of Mato Grosso do Sul (3.8 %) and in Suruí Indians (0.5 %) [8,10,11,12]. Our results are also in agreement with studies performed in other regions worldwide [13,14]. The rate of infestation, in the present study, could be related to a number of factors such as poor hygiene, inadequate sanitation, water intake that was neither filtered nor chlorinated, low education, low socioeconomic status [15,16,17,18].…”
Section: Resultssupporting
confidence: 93%
“…Other groups have also demonstrated a lower prevalence of soil-transmitted helminths compared with H. nana in Peru. 10 Similarly, a study by Tefera and others in eastern Ethiopia showed that while the prevalence of STHs was less than 0.5%, the prevalence of H. nana was 13% in elementary school children receiving regular deworming treatment. 11 Hymenolepis nana has been associated with diarrhea and other gastrointestinal symptoms among children.…”
Section: Discussionmentioning
confidence: 94%
“…Machicado, et al (24), compararon la técnica de sedimentación espontánea en tubo de centrífuga con la Kato-Katz de la OMS y encontraron que ambas tenían la misma tasa de detección de huevos de geohelmintos, pero la primera tuvo un conteo de huevos más alto y, al mismo tiempo, se pueden observar los protozoarios intestinales, a diferencia de la Kato-Katz de la OMS.…”
Section: Discussionunclassified